2000
DOI: 10.1111/j.1651-2227.2000.tb03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor binding protein‐1 as glucose regulator in adolescent boys with type 1 diabetes

Abstract: The aim of the present study was to investigate whether the diurnal variability of B‐Glucose is dependent on GH, IGF‐I and IGFBP‐I levels, apart from insulin, and if there is any difference between Tanner stages 3 and 5. Five boys in Tanner stage 3 and 6 boys in stage 5 with type 1 diabetes were included. Blood was continuously collected from a cubital vein for 24 h. S‐Insulin, S‐GH, S‐IGF‐I and S‐IGFBP‐1 were analysed. B‐Glucose was analysed hourly at bedside. One week before and 1 wk after the 24‐h study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…They found higher IGF-I SDS in pubertal (mean -1.2) than prepubertal (mean -1.6). Also this contrasts our findings in paper IV and our previous work (Zachrisson, Brismar et al 1997;Zachrisson, Dahlquist et al 2000), but it is in line with what others have found (Strasser-Vogel, Blum et al 1995). Taking data from papers I and IV together, recently diagnosed pubertal subjects have IGF-SDS closer to normal than those with a longer diabetes duration, which suggests that endogenous insulin may still have an impact on the levels of IGF-I.…”
Section: Gh-igf-axissupporting
confidence: 79%
See 2 more Smart Citations
“…They found higher IGF-I SDS in pubertal (mean -1.2) than prepubertal (mean -1.6). Also this contrasts our findings in paper IV and our previous work (Zachrisson, Brismar et al 1997;Zachrisson, Dahlquist et al 2000), but it is in line with what others have found (Strasser-Vogel, Blum et al 1995). Taking data from papers I and IV together, recently diagnosed pubertal subjects have IGF-SDS closer to normal than those with a longer diabetes duration, which suggests that endogenous insulin may still have an impact on the levels of IGF-I.…”
Section: Gh-igf-axissupporting
confidence: 79%
“…This is shown to be more prominent in girls and does not affect only nightly GH secretion (Halldin, Tylleskar et al 1998). Circulating IGF-I is lower (Zachrisson, Brismar et al 1997), and IGFBP-1 is further increased (Zachrisson, Dahlquist et al 2000), leading to increased insulin resistance and often to deteriorated metabolic control (Acerini, Williams et al 2001). Increased IGFBP-3 proteolytic activity (IGFBP3-PA) is also present and may play a compensatory role in attenuating the decreased free IGF-I and thus to some extent increasing insulin sensitivity and restoring glycemic control (Zachrisson, Brismar et al 2000).…”
Section: Insulin Deficiency In Relation To the Gh-igf-axis 242mentioning
confidence: 99%
See 1 more Smart Citation
“…In physiological conditions IGF is regulated by GH, insulin and nutrition. The hypoglycaemic potential of circulating IGF (Zachrisson, Dahlquist et al 2000) is reported to be 50 times that of insulin although most of it is inhibited by IGFBP: s (Lewitt 1994). IGFBP-1 has a diurnal rhythm and is regulated by insulin and counter regulatory hormones (Baxter and Cowell 1987;Yeoh and Baxter 1988).…”
Section: Figurementioning
confidence: 99%
“…Regulation of circulating IGF-1 bioavailability is a key function of the IGFBPs [10]. IGFBP-1 has been suggested to modulate the short term bioavailability and activity of IGF-1 [9,10] and plays a role for the glucose homeostasis [12,13]. IGFBP-1 are secreted as phosphoprotein [14], and the affinity of phosphorylated human IGFBP-1 for IGF-I is six fold higher than for the nonphosphorylated protein [14].…”
Section: Introductionmentioning
confidence: 99%